Abdominal visceral and subcutaneous adipose tissues in association with cardiometabolic risk in children and adolescents: the China Child and Adolescent Cardiovascular Health (CCACH) study - Ling Zhang; Min Zhao; Fang Liu; Bo Xi; Shaoke Chen; Junting Liu; Jinghui Sun; Weili Yan; Feng Xiong; Wenqing Ding; Guimin Huang; Jie Mi; et al. (BMJ Open Diabetes Research & Care)
Objective To investigate the association of abdominal visceral adipose tissue (VAT) and subcutaneous adipose tissue (SAT) with cardiometabolic risk factors in children and adolescents.Research design and methods This cross-sectional study consisted of 8460 children and adolescents aged 6–18 years from Chinese urban areas who underwent dual-energy X-ray absorptiometry scan and had metabolic risk factors measured.Results In multivariate analysis adjusted for region, family income, age, puberty development, physical activity, and smoking, VAT and SAT were significantly associated with all metabolic risk factors for both sexes (all p<0.01). After additional adjustment for fat mass index, most of these associations remain significantly positive. In boys, SAT had greater ORs for all risk factors compared with VAT; in girls, however, SAT had greater odds for high triglycerides, smaller odds for high low-density lipid cholesterol, and similar odds for other risk factors compared with VAT. In addition, boys had greater magnitude of associations of SAT with high total cholesterol, high low-density lipid cholesterol, and low high-density lipid cholesterol compared with girls; no sex differences for VAT were observed.Conclusions Both abdominal VAT and SAT have adverse impacts on most of the cardiometabolic risk factors in youth. However, their relative contributions differ between sexes.